Perekonomian Pada Masa Al-Khulafa Al-Rasyidin - Abdul Aziz; Fahmil Fadillah; M. Zeki Abdillah; Putri Nurul Zulia Lubis; Siska Kumala Sari (Perspektif : Jurnal Pendidikan dan Ilmu Bahasa, 2024)
Abu Bakar Ash-Siddiq was one of the Prophet's four companions who rose to prominence as Khulafaur Rasyidin's commanders. Ali bin Abi Talib, Umar bin Khatab, and Uthman bin Affan. Like the development of Islamic economic philosophy, the economic policies of the Rashidun Khulafah are discussed from start to finish. Customs, taxes, zakat, and money printing. During the Rasyidin Khulafah period, the Baitul Maal was built, diwans were made, and other commercial activities took place. to observe and understand the system's progress. This article, which examines Islamic economic policies during the Rasyidin Khulafah era, was composed by employing a method of literary observation drawn from certain publications.